The Role of Mediation and Arbitration in Civil Dispute Resolution - Suratno, Ujang; Utama, Andrew Shady; Dewi, Sandra; HM, Makkah; Wantu, Hasyim Mahmud (Faculty of Law, Universitas Pekalongan, 2024)
Civil dispute resolution is an important aspect of the legal system, aiming to achieve a fair and efficient solution for the parties involved. Mediation and arbitration, as alternatives to out-of-court dispute resolution (ADR), have gained significant popularity in recent years. This systematic literature review aims to examine the role of mediation and arbitration in civil dispute resolution. This study uses a systematic search methodology to identify and analyze relevant studies in various scientific databases. The results of this study conclude that mediation and arbitration are valuable tools for resolving civil disputes. By raising awareness and addressing existing challenges, mediation and arbitration can play a greater role in achieving fair and efficient settlement of civil disputes. Both methods not only reduce the burden on the court, but also increase the participation and satisfaction of the parties to the dispute. Mediation and arbitration provide procedural flexibility that allows for adjustments to the specific context of the dispute, ultimately resulting in better acceptance of the decision. However, the successful implementation of mediation and arbitration is highly dependent on a supportive legal framework and policies that promote its use. Overall, mediation and arbitration are vital components in the modern civil dispute resolution system, with great potential to improve the efficiency and effectiveness of the justice system.